A novel fine spectral structure of solar radio bursts with periodic beaded stripes observed by CBSm of CMP-II - Li, Chuanyang; Chen, Yao; Wang, Bing; Zhong, Ze; Tan, Baolin; Ning, Zongjun; Ning, Hao; Kong, Xiangliang; Chang, Shuwang; Tang, Yanke; Gai, Ning; Deng, Li; et al. (Science China. Physics, mechanics & astronomy, 2025)
A novel fine spectral structure in solar radio bursts has been discovered using the Chashan broadband solar radio spectrometer at meter wavelengths (CBSm), an instrument of the Chinese Meridian Project-Phase II (CMP-II). The structure features periodic narrow-band stripes with a typical recurrence time < 1 s (occasionally reaching 8 s), often drifting from high to low frequencies and accompanied by absorptions, with trailing stripes appearing at the end of preceding ones. Some stripes exhibit periodic beaded (or pearl-like) enhancements with a periodicity of ∼0.1 s. The beaded stripes are reported for the first time ever. Data from the DAocheng Radio Telescope (DART) indicate a radio emission brightness temperature exceeding 10 9 K, originating above brightening loops in active region AR 13664. We proposed a novel generation mechanism of the periodic stripes on the basis of the double plasma resonance (DPR) instability, and explained the beaded substructure in terms of modulation by low-frequency magnetohydrodynamic (MHD) waves. The study highlights the CBSm’s capability to detect high-resolution fine spectral structures and offers novel insights into the emission mechanism and source characteristics of solar radio bursts.